(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2021)
The research aims to show the relationship between the use of automated accounting systems technology and its impact on enhancing the efficiency and effectiveness of the internal control system in a sample of Bahraini universities in light of the rapid changes in the electronic business environment. Automated accounting and its impact on enhancing the efficiency and effectiveness of the internal control system, and it is concluded through the analytical study of the research sample that there is a percentage (93%) of the total respondents agree and fully agree that the use of automated accounting systems in Bahraini universities contributes significantly to enhancing the efficiency of the internal control system and its effectiveness, and the research recommends that it is necessary to use automated accounting systems of all kinds in the field of accounting information systems, because their use will increase the efficiency and effectiveness of these systems and thus will add value and a competitive advantage to the accounting units in Bahraini universities and will have a clear and direct positive impact on the future of those units and individuals working in them . It also recommends the need to raise the scientific and practical qualification of accountants working in universities. The future accountant should have technical knowledge of using automated accounting systems and be familiar with how to use them in order to employ this knowledge when the accounting units choose and determine the types of information and communication technologies to be used that are commensurate with the nature of work those units. It also recommends that the accounting units should develop accounting information systems by introducing the latest automated accounting programs and training accountants on them, whether these programs were designed specifically for the unit or they are ready-made programs and modifications were made to them in proportion to the nature of the unit’s work, without neglecting the interest in the communication network, because the production of The accounting unit of information without delivering it to the beneficiary parties will negatively affect the entire accounting unit, and make it isolated from its environment. Also, when designing a new automated accounting information system for the accounting unit or making an amendment or development of the existing system in it, the accountant should be a member of the design team This is because the responsibility for designing the concepts lies with him, in addition to the need for the accountant to be a member of the analysis team that takes place before starting the design process, because he is one of the most knowledgeable individuals in the details of work within the unit.